2016
DOI: 10.4025/actascitechnol.v38i3.28377
|View full text |Cite
|
Sign up to set email alerts
|

<b>Physiological and hematological responses of Nile tilapia (<i>Oreochromis Niloticus</i>) to different anesthetics during simulated transport conditions

Abstract: ABSTRACT. Minimization of stress during the transportation of live fish is essential in maintaining the welfare and performance of the animals. In order to test the hypothesis that stress during transport of fingerlings of Nile tilapia (Oreochromis niloticus) can be reduced with the aid of the anesthetics menthol, eugenol or benzocaine, we have assessed the effects of these agents at various concentrations on the physiological parameters and survival rates of fish subjected to conditions simulating those norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This kind of result is similar to cortisol and blood glucose level increase at 60 th and 90 th minute on tilapia after electric shock (Barreto & Volpato, 2006), similarly when tilapia is injected with different anesthesia during stress level test (Navarro et al, 2016). This result was also shown on common carp which experienced cortisol increase, but insignificantly after a 12-hour transport (Dobsikova et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This kind of result is similar to cortisol and blood glucose level increase at 60 th and 90 th minute on tilapia after electric shock (Barreto & Volpato, 2006), similarly when tilapia is injected with different anesthesia during stress level test (Navarro et al, 2016). This result was also shown on common carp which experienced cortisol increase, but insignificantly after a 12-hour transport (Dobsikova et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…Repeating and prolonged stress condition might become negative influence towards growth and developing level, immunity, and reproduction mechanism (Schreck & Tort, 2016). Decreasing on stress level during transportation is a crucial aspect to support survival rate and growth performance (Navarro et al, 2016). This aspect can be done through feed supplementation, one of them is chromium (Cr) supplementary in the feed.…”
Section: Introductionmentioning
confidence: 99%
“…With a fixed number of animals available and their welfare in mind, handling was designed to acquire samples with the least amount of anticipated stress for each species and their perceived levels of tolerance to restraint stress. The use of anesthetics has been shown to reduce stress in teleosts ( 43 45 ), although responses are varied and contingent on species and circumstance ( 46 , 47 ). While MS222 can induce cortisol release and alter some other biochemical values in trout ( 47 50 ), it has been shown that it reduces the stress response overall ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher the concentration of this sugar in the blood, the greater the stressful condition of the animal (Eslamloo et al, 2014). Glucose elevation was also observed in tilapia after fish were submitted to other stressors (Moreira et al, 2015;Navarro et al, 2016).…”
Section: Discussionmentioning
confidence: 97%